EFFECT OF CATTLE MANURE VERMICOMPOST ON BEAN ROOT ROT PATHOGENS IN THE GREENHOUSE POT EXPERIMENTS (Journal of Science and Technology, 2025)
The root rot disease in beans is one of the limiting factors affecting common bean production worldwide. Under favourable conditions, the disease can cause yield losses of up to 75%. Control and management strategies of the disease mostly involve the use of fungicides. However, this method is expensive for the majority of farmers, and excessive use of fungicides is detrimental to the environment. Therefore, researchers extensively explore eco-friendly alternatives to minimise adverse effects and the use of synthetic fungicides. One of such options is the use of cattle manure vermicompost. The study was conducted from March to April 2023 at the research greenhouse of the department of plant science of the faculty of agriculture of Chuka University, Kenya. The objective of the study was to determine the effect of cattle manure vermicompost on the severity of root rot in beans in the greenhouse pot experiments. An experimental research design was used to collect data on the effect of cattle manure vermicompost on the severity of pathogens causing bean root rot in the greenhouse pot experiments. Analysis of variance was used to determine if there was a significant effect of cattle manure vermicompost on the severity of root rot pathogens in beans in the greenhouse pot experiments. The Least Significant Difference was used for separation of significant means at α = 0.05. The study findings showed that cattle manure vermicompost significantly reduced the severity of root rot disease in beans during greenhouse pot experiments (p < 0.05). The maximum suppression effect of the disease was observed at a 40% amendment of cattle manure vermicompost, with the lowest disease severity index between 0 and 3.3. Therefore, the management of root rot disease in bean production should incorporate cattle manure vermicompost.